PENGARUH PENGGUNAAN MEDIA INTERAKTIF FLAT PANEL TERHADAP PEMAHAMAN KOSAKATA BAHASA INDONESIA KELAS IV SDN SINDANGSUKA 4. - Esti Sri Novianti; Risma Nuriyanti; Lutfi Asy Ari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Limited vocabulary comprehension among elementary school students can hinder the development of language skills, highlighting the need for innovative learning media that promote student engagement and understanding. This study aimed to examine the effect of interactive flat panel media on the Indonesian vocabulary comprehension of fourth-grade students at SDN Sindangsuka 4. The research employed a quantitative approach using a pre-experimental method with a onegroup pretest–posttest design. The sample consisted of 18 students selected through total sampling. Data were collected through vocabulary comprehension tests, observations, and documentation, and analyzed using descriptive statistics, the Shapiro–Wilk normality test, a paired-sample t-test, and N-Gain analysis. The findings revealed a significant improvement in students’ vocabulary comprehension after the implementation of interactive flat panel media. The hypothesis testing results confirmed a statistically significant effect of the treatment, while the N-Gain score indicated a high level of effectiveness. These findings suggest that interactive flat panel media are effective in enhancing students’ Indonesian vocabulary comprehension. The study implies that technology-based interactive learning media can serve as an innovative alternative for creating more engaging, interactive, and meaningful language learning experiences in elementary education. Keywords: interactive flat panel media, vocabulary comprehension, Indonesian language learning, elementary school students.